Traveller Community Engagement with Local Mental Health Services in Dublin North City and County - Keogh, Brian; Doyle, Louise; Brady, Anne-Marie; Higgins, Agnes; Eustace-Cook, Jessica (School of Nursing and Midwifery, Trinity College Dublin, 2024)
Irish Travellers are an ethnic group, with a long history, traditions, language, culture and customs based on a nomadic tradition which sets them apart from settled people (Pavee Point, 2017). The Central Statistics Office (2016) state that there are around 31,00 Travellers in Ireland. However this figure is likely to be much higher given that there were an estimated 11,680 Traveller families living in Ireland in 2021 (Department of Housing, Local Government and Heritage, 2023). Travellers have been documented as being part of Irish society as far back as the 5th century, where they were referred to as ‘whitesmiths’ due to their association with tin-smithing (Joyce, 2018). Unfortunately, the history of Travellers is largely unrecorded (Claffey et al., 2017). It is well known that Travellers experience multiple social and economic disadvantages and have poorer health outcomes, including mental health (Houses of the Oireachtas, 2021). Mental distress and suicide disproportionally affect the Traveller community with socioeconomic disadvantage, racism and discrimination often cited as the root cause of these problems (Abdella et al., 2010; Houses of the Oireachtas, 2021; McKey et al., 2020; South Dublin Travellers Report, 2021). A review completed by McFadden et al., (2018) found that there were a range of factors that influenced Traveller use of the health services including the mental health services and a summary of these is presented it table 1.1.
PUBLISHED